2007
DOI: 10.1111/j.1365-2486.2007.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale climatic signatures in lakes across Europe: a meta‐analysis

Abstract: Recent studies have highlighted the impact of the winter North Atlantic Oscillation (NAO) on water temperature, ice conditions, and spring plankton phenology in specific lakes and regions in Europe. Here, we use meta-analysis techniques to test whether 18 lakes in northern, western, and central Europe respond coherently to winter climate forcing, and to assess the persistence of the winter climate signal in physical, chemical, and biological variables during the year. A meta-analysis approach was chosen becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
195
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(205 citation statements)
references
References 71 publications
9
195
0
1
Order By: Relevance
“…These expectations were confirmed in the freshwater experiments, that is, the magnitudes of phytoplankton and Daphnia peaks were unaffected by temperature, but increased with increasing light supply. While field observations have shown higher abundances of Daphnia in warm (high NAO) years (Straile 2002), this trend can be attributed to shifts in timing of spring maxima rather than to overall increases in abundance (Blenckner et al 2007), which is consistent with our results. Overall, the results indicate that light limitation had pronounced effects on plankton succession in lentic experiments and suggests that tight predator-prey coupling can suppress a response of phytoplankton and grazer peaks to increased temperature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These expectations were confirmed in the freshwater experiments, that is, the magnitudes of phytoplankton and Daphnia peaks were unaffected by temperature, but increased with increasing light supply. While field observations have shown higher abundances of Daphnia in warm (high NAO) years (Straile 2002), this trend can be attributed to shifts in timing of spring maxima rather than to overall increases in abundance (Blenckner et al 2007), which is consistent with our results. Overall, the results indicate that light limitation had pronounced effects on plankton succession in lentic experiments and suggests that tight predator-prey coupling can suppress a response of phytoplankton and grazer peaks to increased temperature.…”
Section: Discussionsupporting
confidence: 82%
“…Chrysophytes, which contributed only a small proportion to overall biomass in both systems, were the least responsive to warming. Similar to primary producers, peak timing of micro-and mesozooplankton species advanced at increased temperature, which is consistent with widespread observations in freshwater and marine systems (Blenckner et al 2007;Straile 2002;Thackeray et al 2010). Overall, the successional pattern suggests that zooplankton responded more strongly to warming than phytoplankton, as indicated by the faster acceleration of initial population growth rates in high temperature treatments (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…as long as 8-10 years depending on the internal loading from sediments and the limited P exchange between water layers in meromictic lakes compared to holomictic lakes. Blenckner et al (2007) found a decreasing general effect on winter and spring TP concentrations in lakes from climate change but no effects on summer TP concentrations, although it was stressed in this meta-analysis that any effects may vary from lake to lake depending on catchment area characteristics and differences in sedimentwater dynamics. The climate change scenarios in the present study (Figs 8 and 9) showed that the projected changes in runoff would only marginally affect TP concentrations in Lake Bourget.…”
Section: Discussionmentioning
confidence: 94%
“…Temperature increases could have a slightly greater effect (a possible 4.6% increase in TP concentrations from a 4.5ºC increase in surface water temperature), although the discussed model uncertainties of up to 35% suggest that our projections associated with temperature increases should be interpreted with care. Both sedimentation and diffusion are spurred by increasing temperatures (Håkanson and Bryhn, 2008) and decreasing TP concentrations as suggested by Blenckner et al (2007) would probably be more likely in shallow lakes where ET bottom types dominate and diffusion is less important than in Lake Bourget. The greatest effects from climate change on TP concentrations in this lake would most probably occur if the TP loading would be significantly affected by changes in runoff or temperature.…”
Section: Discussionmentioning
confidence: 99%
“…However, as soil temperature is a dominant driver, opposing inter-annual patterns in NO 3 -leaching may be observed in regions normally blanketed by snow in winter when they lack snow cover, since snow cover insulates the uppermost soil layer from the atmosphere (Groffman et al 2009;Makoto et al 2013). Consequently, relationships between NO 3 -leaching and the NAO index in the UK and in northern Europe may vary regionally (George et al 2004;Blenckner et al 2007;de Wit et al 2008).…”
Section: N Leaching In Dormant Seasonmentioning
confidence: 99%